The family Carabodidae (Acari, Oribatida) VIII. The genus Machadocepheus (first part) Machadocepheus leoneae sp. n. and Machadocepheus rachii sp. n. from Gabon - Fernandez, Nestor (2014)
The genus Machadocepheus, being one of the more complex genera of the Carabodidae family, is briefly outlined to demonstrate this complexity. Descriptions of two new species from Gabon, M. leoneae sp. n. and M. rachii sp. n. are given.